2015
DOI: 10.1186/s12889-015-1940-x
|View full text |Cite
|
Sign up to set email alerts
|

Does parental monitoring moderate the relationship between bullying and adolescent nonsuicidal self-injury and suicidal behavior? A community-based self-report study of adolescents in Germany

Abstract: BackgroundBeing a victim of bullying in school is clearly linked to various social, emotional, and behavioral problems including self-harm behavior. However, it is not known whether even occasional victimization has similar negative consequences and whether protective factors such as social support may prevent those harmful developments. The present study therefore focuses on the nonsuicidal self-injury (NSSI) and suicidal behavior (SB) in victims of bullying and the potentially moderating effect of parental m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
48
1
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 38 publications
1
48
1
7
Order By: Relevance
“…The use of nicknames that degrade the image of the adolescent, verbal provocation and sexual harassment characterises episodes of school bullying (16,17). Victims of verbal school bullying may suffer from depression, anxiety or even commit suicide (18)(19)(20)(21)(22)(23). The teenager who suffers bullying is more prone to suicide than others who are not involved in episodes of bullying (18).…”
Section: Introductionmentioning
confidence: 99%
“…The use of nicknames that degrade the image of the adolescent, verbal provocation and sexual harassment characterises episodes of school bullying (16,17). Victims of verbal school bullying may suffer from depression, anxiety or even commit suicide (18)(19)(20)(21)(22)(23). The teenager who suffers bullying is more prone to suicide than others who are not involved in episodes of bullying (18).…”
Section: Introductionmentioning
confidence: 99%
“…National and international studies highlight the consequences of bullying in the short and long term in the lives of children and adolescents who experience this situation [11][12][13] , interfering in cognitive and socioemotional development, whether as victims, aggressors, or even spectators of such events. When suffering bullying, children and adolescents are more exposed to difficulty concentrating, low self-esteem, anxiety, depression, suicidal ideation, attempted suicide, consummate suicide, self-harm, and psychological stress [12][13][14][15][16][17] . A study developed in the countryside in Southeast Brazil identified that adolescents who are victims of bullying present emotions such as feelings of anger, discouragement, sadness, and shame 11 .…”
Section: Introductionmentioning
confidence: 99%
“…A study developed in the countryside in Southeast Brazil identified that adolescents who are victims of bullying present emotions such as feelings of anger, discouragement, sadness, and shame 11 . It has been shown that the effects of bullying interfere with the way of life of children and adolescents, affecting even the school performance of this age group 12,13,[16][17][18] . In Brazil, young male adolescents are more subject to bullying, associated with risk situations, such as domestic violence, among others, which suggests a need for a holistic approach from education and health professionals, parents, and the community in the search for preventive measures 10 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to conceptual differences, another aspect that generates disagreement is the definition of a cut-off point for bullying, that is, the minimum frequency capable of transforming a violent school event into bullying. [12][13] The construction of a scientific consensus would contribute to the formulation of the understanding of the phenomenon, since studies show a direct relationship between the consequences of involvement in bullying and the frequency, duration and severity of these actions. 14 Considering these scientific weaknesses and the impact on the health of children and adolescents, it is necessary to identify the elements that contribute to the emergence and propagation of bullying.…”
Section: Introductionmentioning
confidence: 99%